Process of preparing regioregular substituted thiophene polymers - Heeney,M; Mcculloch,I; Giles,M; Koller,G; Zhang,W (2006)
A process of prepg. a polymer from an optionally substituted thiophene having at least two groups that are capable of reacting with magnesium, comprises reacting the thiophene with magnesium in the presence of a catalytic amt. of an organohalide or organomagnesium halide to form a regiochem. Grignard intermediate or a mixt. of regiochem. Grignard intermediates, and polymg. the Grignard intermediate(s) in the presence of a suitable catalyst. The polymers typically have head-to-tail configuration. The polymers are useful as semiconductors or charge transport materials in optical, electrooptical or electronic devices including field effect transistors (FETs), electroluminescent, photovoltaic and sensor devices, to FETs and other semiconducting components or materials comprising the novel polymers.